PLANTING THE SCIENCE SEED: ENGAGING STUDENTS IN PLACE-BASED CIVIC ACTIONS - O’Connor, Kevin; Sharp, Robert (European Scientific Journal, ESJ, 2014)
As teacher educators, we are interested in examining the extent to which science education programs based on principles of place-based and experiential education engage students in the study of science and the application of science to issues of civic concern. A great deal of research confirms that science education programs have generally been ineffective in producing students who understand and successfully apply science concepts and knowledge to social issues. This research examines the extent to which public school programs incorporating place-based and experiential learning through extended field experiences and integrated coursework have led to engaging students in science and related civic actions.